Pertumbuhan Beberapa Bentuk Potongan Pangkal Setek Tanaman Mawar (Rosa sp.) Akibat Cara Aplikasi Zat Pengatur Tumbuh Root-Up - Wendi Yuliawan (Paspalum: Jurnal Ilmiah Pertanian, 2019)
The research aims to study the growth of rose cuttings due to the shape of the base of cuttings and the way of Root-up application. The experiment was carried out in Screen House in Pasirbanteng, Hegarmanah Village, Jatinangor District. Sumedang Regency. The experiment was conducted from March to August 2015. The methode based on Randomized Block Design consisting of two factors. The first factor is the Root-up (W) application method which consists of 3 factor levels, namely without root up (w1), powder (w2), and paste (w3). The second factor is Form Cutting (S) consisting of 3 levels of treatment, is the oblique sliced (s1), taper sliced (s2), and flat sliced (s3). The factors composed of nine combinations of treatments, each of which was repeated 3 times. The results show that was not the interaction between the shape of cuttings and Root-up applications on the growth response variables of cutting rose plants, is number of shoots, length of shoots, root length, number of roots, and root volume. The oblique sliced and tapered slice form the base and of the cutting shave the best effect on the length of shoots of rose plants cutting